CEO Ownership, Stock Market Performance, and Managerial Discretion - LILIENFELD‐TOAL, ULF VON; RUENZI, STEFAN (Journal of Finance, 2014)
ABSTRACT We examine the relationship between CEO ownership and stock market performance. A strategy based on public information about managerial ownership delivers annual abnormal returns of 4% to 10%. The effect is strongest among firms with weak external governance, weak product market competition, and large managerial discretion, suggesting that CEO ownership can reverse the negative impact of weak governance. Furthermore, owner‐CEOs are value increasing: they reduce empire building and run their firms more efficiently. Overall, our findings indicate that the market does not correctly price the incentive effects of managerial ownership, suggesting interesting feedback effects between corporate finance and asset pricing.